Public Perception of the Fifth Generation of Cellular Networks (5G) on Social Media - Dashtipour, Kia; Taylor, William; Ansari, Shuja; Gogate, Mandar; Zahid, Adnan; Sambo, Yusuf; Hussain, Amir; Abbasi, Qammer H.; Imran, Muhammad Ali (Frontiers in Big Data, 2021)
With advancement of social media network, there are lots of unlabelled reviews available online, therefore its necessarily to develop an automatic tools to classify these types of reviews. For utilising these reviews for user perception, there is a need for automated tools that can process online user data for optimising user perception. In this paper, a novel sentiment analysis framework has been proposed to identify people's perception towards mobile networks. The proposed framework consists of three basic steps: preprocessing, feature selection and applying different machine learning algorithms. The performance of the novel framework has taken into account different feature combinations. The simulation results show that the best performance is by integrating unigram, bigram and trigram features.